Placental Morphometry and Newborn Outcomes in Pregnant Women Infected with Malaria - Mogan, Martina; Yogi, Ruth; Trisnawati, Endang (Ahmar Metastasis Health Journal, 2025)
Malaria during pregnancy is a serious health problem that can negatively affect both the mother and the fetus. Malaria infection in pregnant women can disrupt the supply of nutrients and oxygen to the fetus, potentially resulting in low birth weight. This condition is caused by changes in the infected placenta, which affect the transfer of essential nutrients to the fetus. This study aimed to analyze the effect of malaria during pregnancy on placental morphometry and newborn outcomes at Sentani Primary Health Care Center, Jayapura Regency. This study employed an observational analytic method with a cross-sectional design and was conducted over a period of three months. Sampling was carried out using purposive sampling. The study population consisted of pregnant women in labor who were infected with malaria or had a history of malaria infection during the second and third trimesters of pregnancy. The sample included 30 women in labor (15 pregnant women with malaria and 15 normal pregnant women), whose placental morphometry and newborn outcomes were measured. The statistical analysis used was the Chi-square test. The results showed that malaria during pregnancy had a significant effect on placental size in newborns (p-value = 0.023) and on newborn birth weight (p-value = 0.035), while no significant effect was found on newborn body length (p-value = 0.243). In conclusion, placental size in pregnancies complicated by malaria was smaller than in normal pregnancies, and malaria infection during pregnancy affected placental morphometry and newborn birth weight at Sentani Primary Health Care Center, Jayapura Regency.